Bilateral Juvenile Cataract in Childhood: A Comprehensive Clinical and Surgical Approach - Imelda, Eva; Lubis, Dara Amalia; Lathifah, Lakaeisya SY; Toshniwal, Nikhil; Adev, Sarra Mutiara (Heca Journal of Applied Sciences, 2025)
Juvenile cataracts, though less common than congenital types, can cause irreversible visual impairment if diagnosis and treatment are delayed. We report a 10-year-old boy with progressive bilateral visual loss, photophobia, and leukocoria over three years, with a positive paternal history suggesting hereditary etiology. Examination revealed dense bilateral lens opacities and markedly reduced visual acuity. The patient underwent sequential aspiration–irrigation with posterior chamber intraocular lens implantation in both eyes. Surgeries were uneventful; however, postoperative vision in the right eye remained limited due to deprivation amblyopia, while the left eye achieved a better functional outcome. Final refraction showed mild residual error, and the patient was continued on visual rehabilitation and amblyopia therapy. This case highlights the importance of early detection and timely surgery in pediatric cataract to prevent permanent visual deficits and optimize outcomes. This report aims to illustrate the impact of delayed intervention on functional vision, daily activities, and educational performance in school-aged children within resource-limited settings.